Primary osteosynthesis augmented with autologous bone graft with total knee arthroplasty in patients with stress fractures of medial femoral condyle with knee osteoarthritis: a cost effective approach - Shah, Vikram Indrajit; Shah, Kalpesh; Upadhyay, Sachin (International Journal of Research in Medical Sciences, 2017)
Background: We report six cases of an arthritic knee with stress fractures of medial femoral condyle causes substantial pain in the medial compartment severe enough to hamper their routine activities. Suggestive findings were appreciated on Skiagram in only one case, in rest was diagnosed by magnetic resonance imaging (MRI). These are likely underdiagnosed and frequently mistaken for primary osteonecrosis. The present report showed that the early detection and treatment of stress injuries in an arthritic knee is imperative to ensure best possible outcome. Methods: Six patients with a mean age of 73.1±5.7 years were registered with an arthritic knee with stress fracture of medial femoral condyle. Primary osteosynthesis augmented with autologous bone-graft with total knee arthroplasty (TKA) done in all patients. All patients were followed up until they became asymptomatic, displayed radiographic healing, and had recovered full range of motion with no pain. Pre and post-operative western ontario and mc-master universities osteoarthritis index (WOMAC) score were recorded and compared. The level of significance was set at 0.05 levels. Results: Mean follow-up was 7.0 years. All patients showed statistically significant improvement in their WOMAC total scores (p <0.05). Stress fractures united with good knee alignment. All patients had recovered full range of motion with no pain at the time of final follow-up. No adverse events were noted in any of the patient treated. Conclusions: The present approach is a successful procedure for the elderly population with an arthritic knee with stress fracture of medial femoral condyle. Return to pre-morbid level of functional activity occurs very swiftly.